THE ROLE OF THE PHARMACIST IN PREVENTING THE ABUSIVE USE OF PSYCHOTROPICS IN PATIENTS WITH MENTAL DISORDERS (CIPEEX, 2024)
Mental disorders are legitimate medical conditions that affect human thoughts and emotions. As a form of treatment, psychotropic drugs are used—substances designed to act on the brain, altering our way of feeling, thinking, and behaving. However, while psychotropics can offer various public health benefits, their prolonged use can lead to chemical dependence, resulting in compulsive behavior and impairment in personal and social aspects. Therefore, pharmacists have the role of guiding users of psychotropic medications during pharmaceutical care so that patients can understand all the risks of side effects that these medications may entail. To analyze the mechanisms of action of psychotropic drugs, how these medications affect the central nervous system and influence mental state and psychological functioning, and the risks associated with their use and abuse through a bibliographic research. A search was conducted in the databases PubMed, BVS, and Scielo using the specified descriptors: psychotropics, prevention, abuse, and mental disorders. The search was carried out using criteria for excluding and accepting articles published within the last five years in two languages, English and Portuguese. Three articles per platform were found and used for the study. The studies highlight that the implementation of monitoring programs led by pharmacists is essential for reducing incidents of psychotropic abuse among patients with mental disorders. Regular follow-up and prescription reviews were cited as crucial factors in the early identification of abuse signs. Conclusion: Furthermore, pharmaceutical follow-up is essential for reducing adverse reactions and drug interactions, improving treatment adherence, and enhancing patients' quality of life.
Keywords: psychotropics; pharmacists; abusive use; mental disorders